Manpower planning workbook - Pettman, B. O.; Tavernier, Gerard (Aldershot, Hants, England ; Brookfield, Vt., U.S.A. : Gower Pub. Co., 1984)
This book is intended to stimulate readers - senior personnel managers and others interested in manpower planning in the broadest sense of the term - to go out and obtain the data required to complete the forms illustrated and thereafter to analyze the data. The text is almost wholly concerned with describing methods and procedures for obtaining and analyzing the data on the illustrations and any knowledge contained in the text is of little value unless the recommendation are followed.
Includes index.
Includes bibliographical references p. 121-124
hza 19/07/2018
Loan
Keywords: Manpower planning